Analisis Minat Belajar Peserta Didik pada Pembelajaran Seni Rupa di Kelas V Sekolah Dasar - Maharani Arif, Asila; Andaryani, Eka Titi; Sutikno, Putri Yanuarita (UNIVERSITAS INDO GLOBAL MANDIRI, 2025)
The problem in learning fine arts is that it is considered as unimportant learning so that it has a low interest perspective. Students assume that fine arts is an extracurricular activity so that learning does not require more focus and is done casually.. Based on the Learning Outcomes (CP) set, fine arts learning at the basic education level examines the elements of rupa and design principles in the environment around students. This study aims to determine the learning interest of grade V elementary school students in learning fine arts. In addition, this study also aims to describe the factors that influence interest in learning fine arts. The method used in this research is a combination method with a descriptive qualitative approach. The instruments were observation, questionnaire, and interview. The subjects of this study were the homeroom teacher of grade V elementary school and 10 grade V students. Data collection on interest in learning fine arts learning was obtained from the results of distributing questionnaires of interest in learning to grade V students and information on factors that influence interest in learning was obtained by observing and interviewing teachers. The results of this study indicate that based on indicators of student interest in learning fine arts obtained 66% with high indicators. Supported by the results of interviews that the high interest in learning fine arts learning is caused by the talents of students, teacher support in learning, and adequate facilities